BRANDING RUMAH LIMAS 100 TIANG DI OGAN KOMERING ILIR SUMATERA SELATAN - m.baqifidynillah; Aji Windu Viatra; Heri Iswandi (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract: This 100-Pole Limas House has its own charm and uniqueness because it has 100 pillars and foundations. According to (Hartini, 2016) The forms of the carving motifs on the Hundred Pillar House are generally geometric in shape, such as triangle shapes, rectangles, circle shapes, parallelogram shapes, with carvings such as slampit garang, wave shapes, fan leaves, jasmine stalks and sowing seruje. Flora such as allied rose motifs, sow flowers, tulips, mangosteen leaves, melon and lotus flowers. Fauna is like an elephant's trunk motif. Other natural motifs with shapes such as tongues, flames (China), flames (Kayuagung), morning stars, and sunrises. Even the 100 Pillar Limas House has historical value and keeps a unique story behind its construction. Even though it has been standing for hundreds of years, the house is still there and is well maintained by local residents. The current situation, some people prefer to build houses in a modern way so that there is a lack of preservation of traditional houses, one of which is the 100-pole pyramid house. 100 pillar pyramid house in Ogan Komering Ilir.